Videojuego y su repercusión en el comportamiento de un adolescente de 13 años - García Paredes, Fernanda Ivelice (2021)
The current case study reveals a valid problem today, the problem is video games, which produce emotional symptoms such as sadness, anger and behavior (such as aggression) and poor academic performance. This affects patients in the social, family and educational environment. By gathering information, and through the use of clinical history, psychological tests and interviews, the corresponding clinical diagnosis is achieved. To be able to check if video games have greatly interfered with the correct development of the patient. Finally, it is expected that the proposals offered as treatment options in the family and cognitive-behavioral systems will help greatly to improve inappropriate behaviors, thus reducing the appearance of problems.